Quercetin Improves Baroreflex Sensitivity in Spontaneously Hypertensive Rats - Monteiro, Matheus M. O. (Molecules, 2012)
Quercetin is a well-known antioxidant. Here, we investigated the effects of treatment with quercetin on mean arterial pressure (MAP), heart rate (HR) and baroreflex sensitivity (BRS) in spontaneously hypertensive rats (SHR). SHR and their controls (WKY) were orally treated with quercetin (2, 10 or 25 mg/kg/day) or saline for seven days. On the 8th day, MAP and HR were recorded. BRS was tested using phenylephrine (8 mg/kg, i.v.) and sodium nitroprusside (25 mg/kg, i.v.). Oxidative stress was measured by tiobarbituric acid reactive species assay. The doses of 10 (n = 8) and 25 mg/kg (n = 8) were able to decrease the MAP in SHR (n = 9) (163 ± 4 and 156 ± 5 vs. 173 ± 6, respectively, p < 0.05) but not in WKY (117 ± 1 and 118 ± 2 vs. 113 ± 1, respectively, p < 0.05). The dose of 25 mg/kg/day increased the sensitivity of parasympathetic component of the baroreflex (−2.47 ± 0.31 vs. −1.25 ± 0.8 bpm/mmHg) and decreased serum oxidative stress in SHR (2.04 ± 0.17 vs. 3.22 ± 0.37 nmol/mL, n = 6). Our data suggest that treatment with quercetin reduces hypertension and improves BRS in SHR via reduction in oxidative stress.